ANALYSIS OF THE RECOVERY OF IMPORT-EXPORT ACTIVITIES IN SUSTAINING ECONOMIC STABILITY BEFORE AND DURING THE COVID-19 PANDEMIC IN INDONESIA - Anggun Putri; Rangkuty, Dewi Mahrani (TRANSACTION: Journal of Taxation, Accounting, Management and Economics, 2023)
The purpose of this study is to look at export and import activities in supporting economic stability before and during the pandemic. The method used is VAR and Difference Test. The results of the VAR research show that Export and Import activities contribute to each other and are optimal in supporting economic stability in Indonesia, both in the short, medium and long term. The results of the FEVD show that the policies used in Export activities are in the short term carried out by Exports themselves, then in the medium and long term the policies used in maintaining Export activities are Exports themselves and are influenced by Imports. Then the results of the FEVD show that the policy in maintaining imports in the short, medium and long term is with imports itself and followed by exports. Then the results of the Difference Test show that there are no significant differences in inflation and exchange rates before and during the Covid-19 pandemic. If there is an error in taking action on Exports and Imports, it can make the economy unstable. Thus, in sustaining economic stability in Indonesia, the Government must monitor and take the right policies, both by reducing and increasing exports and imports. Where if you take the wrong action, it will have a huge impact on the Indonesian economy. Then for the future the Central Bank to maintain stable inflation and exchange rates, so that the economy is maintained.